1983
DOI: 10.1111/j.1365-2923.1983.tb00963.x
|View full text |Cite
|
Sign up to set email alerts
|

Medical education about human sexuality: the impact of film in the workshop setting

Abstract: Summary The current study uses a pre‐test‐post‐test control group design in which students who were volunteer participants were randomly assigned, controlled for sex, to one of two 1‐day human sexuality workshops (n=19, n=21) or a control group (n=17). The two workshops were identical in format and content. Each included four topic areas: homosexuality, psychosexual development of the male and female, masturbation, and the meaning of touch. After introduction to topic areas in large group sessions, small group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Other themes were the technical aspects of using cinema for teaching,9 human sexuality,10 clinical pharmacology,11 paediatrics,12 general medicine,13 AIDS14 and group counselling 15…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other themes were the technical aspects of using cinema for teaching,9 human sexuality,10 clinical pharmacology,11 paediatrics,12 general medicine,13 AIDS14 and group counselling 15…”
Section: Resultsmentioning
confidence: 99%
“…Medical students featured very heavily7 10 11 13 25 29 31 33 47 49 51 53 57 58 63 65 68–70 along with psychiatry residents 8 18–20 22 24 26 30 71. Other targeted groups included clinical teachers,34 40 42 nursing students,12 43 medical13 72 and family medicine residents,45 66 counselling students23 and broader allied health undergraduates 39…”
Section: Resultsmentioning
confidence: 99%
“…31,89 However, a controlled study reported in 1983 that students who participated in small group workshops that incorporated sexually explicit material did not fare better on the knowledge and attitudes components of a validated scale for sexuality knowledge and attitudes than students who participated in workshops without explicit material. 90 Use of explicit material is less common in modern medical education, and when it is used, a relative minority of students report that it is beneficial. 33 Indeed, exposure to sexually explicit material without proper context and supervision might lead to worsened prejudice.…”
Section: Immersion and Desensitizationmentioning
confidence: 99%
“…Hollywood movies, documentaries, and short films were screened in full or shown as clips to teach students on topics such as professionalism [ 21 , 22 , 33 ], ethics [ 34 – 36 ], cultural competence [ 5 , 37 , 38 ], managing severe or terminal disease [ 23 , 24 ], breaking bad news [ 14 ], death and dying [ 24 ], and alcohol and other drugs [ 39 , 40 ]. The subjects of sexuality [ 41 ] and clinical pharmacology [ 42 ] were raised in select studies. Specific disease topics mentioned were cancer [ 24 ], epilepsy [ 29 ], and AIDS [ 23 ].…”
Section: Resultsmentioning
confidence: 99%